A Bibliometric Analysis of Medullary Thyroid Carcinoma From 2000 to 2022 - TAN Meijuan; YANG Shijie; XU Xiequn (Xiehe Yixue Zazhi)
ObjectiveTo review the state of research on medullary thyroid carcinoma (MTC) over the past two decades, so as to offer a quick reference for understanding the current state and future trends in this field.MethodsA computer was employed to search the Web of Science Core Collection database for MTC-related literature (types: articles and reviews) published between 2000 and 2022. VOS viewer 1.6.18 software was utilized to create collaboration network diagrams, heat distribution diagrams for high-yielding countries(with publication volume ≥90), research institutions (with publication volume ≥60), and authors (with publication volume ≥30), and high-frequency keyword clustering network diagrams. Cite Space 5.7.R5 software was employed to conduct cluster analysis and explosive keyword detection on co-cited literature.ResultsA total of 4866 MTC related literature (3688 articles and 918 reviews) were obtained. Although the annual publication volume fluctuated, the overall trend showed a gradual increase. The 4866 articles are from 87 countries, involving 4250 research institutions, 21 016 authors, and 963 journals. The United States (1436 articles), MD Anderson Cancer Center at the University of Texas (139 articles), and Dralle H (Department of General Surgery at Halle Wittenberg University Hospital, 61 articles) were the countries, research institutions, and authors with the highest number of publications, respectively. High frequency keywords form four clusters: RET gene expression, prognostic factors, MTC clinical management, and MTC treatment. The keywords emerging explosively in recent years were management, survival, guideline, association, etc. The key areas of focus in highly cited literature were RET proto oncogene, targeted therapy, RET gene mutation, and so on.ConclusionsIn the past 20 years, MTC related research has shown a gradual upward trend, with developed countries led by the United States taking a leading position in this field. The current research hotspots are the treatment, diagnosis, application of inhibitors, and exploration of the pathogenesis of MTC.